The Effectiveness and Efficiency of Cash Waqf Management in Tabung Wakaf Indonesia - Rusny Istiqomah Sujono; Febrian Wahyu Wibowo; Mu'inan Rafi'; Ambar Musoffi (ITB AAS INDONESIA Surakarta, 2022)
Nazhir is one of the key factors in the success of waqf management institutions. Therefore, it is necessary for Nazhir to understand and assess the effectiveness and efficiency of cash waqf management performance. One of the nazhir cash waqf that has been active for a long time is Tabung Wakaf Indonesia. The research method used in this study is an analysis of institutional management by analyzing the financial report of Tabung Wakaf Indoensia from year 2013-2019. Based on the results of the analysis, it was found that the value of efficiency and effectiveness of Tabung Wakaf Indonesia was fluctuating, considering that the profit sharing was uncertain, therefore it was necessary to strengthen institutions such as reforming institutions and regulations, increasing resources (nazhir) by conducting training and studying existing research in assessing and producing cash waqf.